2019
DOI: 10.2298/sos1904363o
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of MgAl2O4 sintered ceramics

Abstract: Single phase MgAl 2 O 4 was made from a one-to-one molar ratio of MgO and Al 2 O 3 powders mixed using ball-milling. Mixtures of MgO and Al 2 O 3 were subsequently treated in planetary ball mill for 30, 60, 90 and 120 minutes in air. The aim of this study was to examine phase composition, microstructure, and densification behavior of sintered specimens. After sintering in dilatometer at 1500 °C, the powder was converted to single phase MgAl 2 O 4. The results show that mechanical activation improved the densif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…Numerous analysts have put forth different attempts in creating transition metal based oxide (essentially got from Mn 3 O 4 ) nanoparticles through various synthesis techniques, for example, ultrasonic technique [21],co-precipitation [22,23], auto-burning [24], solid state reaction [25,26], ball milling process [27,28], sol-gel [29] techniques and others. In light of the methods referenced above, we apply the co-precipitation route because of its simplest and adequacy in creating the nanomaterials.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous analysts have put forth different attempts in creating transition metal based oxide (essentially got from Mn 3 O 4 ) nanoparticles through various synthesis techniques, for example, ultrasonic technique [21],co-precipitation [22,23], auto-burning [24], solid state reaction [25,26], ball milling process [27,28], sol-gel [29] techniques and others. In light of the methods referenced above, we apply the co-precipitation route because of its simplest and adequacy in creating the nanomaterials.…”
Section: Introductionmentioning
confidence: 99%
“…Powder mixtures milled for 60 h, pressed, and sintered at 1200 • C for 1 h gave a cold crushing strength value of 70 MPa. 71 Another study by Obradović et al 72 reported on the formation and…”
Section: Synthesis Of Mas By Solid-state Reaction Routementioning
confidence: 98%
“…The crack process in Ca-PWA crystals had followed the appearance of smaller crystals with the average size of several micrometers (~ 2 μm). Concerning Ca-PWB sample, SEM image have shown increased micrometer size (~ 20 μm) due to agglomeration of crystals [33][34][35][36].…”
Section: Tab IImentioning
confidence: 99%